M.O. Mbatha: Isichazamazwi SesiZulu - Masubelele, Rose (Lexikos, 2007)
1. Introduction: Comprehensiveness / Representativeness of the dictionary This is a significant and commendable contribution to the development of Zulu lexicography in general, and Zulu monolingual dictionaries in particular. There could not have been a better time for the publication of such a work dealing with a language whose lexicon expands daily. As stated by the editor, this work was started at the University of KwaZulu (oNgoye) in 1997 and resulted in two volumes edited by Prof. A.C. Nkabinde, namely Isichazamazwi I and Isi-chazamazwi II which appeared in 1982 and 1985 respectively. According to the editor, Isichazamazwi SesiZulu is an extension of the previous two volumes. However, because of the many changes and additions made to these volumes, it was decided to integrate these into the present compilation, consisting of about 21 000 entries.